The trunk extensor flexor relationship in men and women by isokinetic dynamometry - Simbala, Marcia; Czaikoski, Camila Ksaveria; Eduardo, Fernanda Maria Cercal; Moser, Auristela Duarte Lima; Bernardelli, Rafaella Stradiotto (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: The thoracolumbar musculature plays a key role in the balance and stability of the pelvis. The isokinetic dynamometer provides accurate assessment of muscle performance and treatment guidance. Objective: To compare the flexors / extensors of the trunk link between sedentary men and women, asymptomatic by isokinetic dynamometry. Method: An observational cross-sectional study. The sample consisted of 100 asymptomatic sedentary volunteers, 50 males and 50 females with a mean age of 22.2 ± 3.3 years. The collection was made in the center of isokinetic dynamometry of the university grew. The Cybex Norm isokinetic dynamometer Model 7000 ™, trunk module was used. The subjects were weighed and measured, made global warming a 5 minutes cycle ergometer unloaded. Tested the flexor and extensor muscles in concentric and eccentric contractions, with an interval of three minutes between each assessment. We adopted a range of 10 degrees of extension to 70 degrees of flexion, with five repetitions at angular velocity 60 ͨ / s performing maximal strength. Familiarity with the equipment was done in the way of submaximal intensity contraction. The analysis was performed using SPSS, version 20.0 (p <0.05). Results: muscle ratio for females was higher compared to males, demonstrating in men greater deficit flexors compared to extensors of the trunk. Conclusion: no significant neither for females nor for males difference. Confirming that the ratio of muscle strength agonist/antagonist of a joint should not change regardless of the mode of contraction is tested.